DETERMINAN STRUKTUR MODAL DALAM PERSPEKTIF PECKING ORDER THEORY PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Siti Kholifah; Sumani Sumani; Novi Puspitasari (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the effect of firm size, business risk, asset growth, and profitability on capital structure and to examine the application of Pecking Order Theory (POT) in the companies. The population was all food and beverage companies listed in Indonesia Stock Exchange (IDX) in 2014-2016. This research used purposive sampling technique with the sample consisted of 14 companies. Data were sourced from the company financial reports published on IDX's website. Data were analyzed using multiple linear regression. The results showed that profitability had a significant effect on capital structure, while firm size, business risks, and asset growth did not affect the capital structure of the firm. Related to the application of POT, the results showed that there were 6 companies applying POT in 2014, 7 companies applying POT in 2015, and 8 companies applying POT in 2016. Keywords : Capital structure, pecking order theory, food and beverage company